Good Governing - Rodriguez, Daniel B. (Cambridge University Press, 2025)
Drawing upon law, history, and social science, this book is a close investigation of an important yet neglected area of constitutional law: the state police power and its function in regulatory governance in the US It is a major contribution to state constitutional law literature and contemporary regulatory policy.